2013
DOI: 10.1039/c3dt50462j
|View full text |Cite
|
Sign up to set email alerts
|

Ion pumps as biological targets for decavanadate

Abstract: The putative applications of poly-, oligo-and mono-oxometalates in biochemistry, biology, pharmacology and medicine are rapidly attracting interest. In particular, these compounds may act as potent ion pump inhibitors and have the potential to play a role in the treatment of e.g. ulcers, cancer and ischemic heart disease. However, the mechanism of action is not completely understood in most cases, and even remains largely unknown in other cases. In the present review we discuss the most recent insights into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 63 publications
0
58
0
Order By: Relevance
“…IC50 concentrations for these drugs on this transporter have been reported to be 0.2-3 M and 0.03 M, respectively (1,18). Ryanodine and tetracaine were used to block ryanodine receptor ER Ca 2ϩ channels.…”
Section: Animals Kitmentioning
confidence: 99%
“…IC50 concentrations for these drugs on this transporter have been reported to be 0.2-3 M and 0.03 M, respectively (1,18). Ryanodine and tetracaine were used to block ryanodine receptor ER Ca 2ϩ channels.…”
Section: Animals Kitmentioning
confidence: 99%
“…Metal-substituted POMs have been used as catalysts in several catalytic reactions, ranging from the epoxidation of olefins and alkanes to the splitting of water [26][27][28][29]. Additionally, POMs exhibit biological activity, which includes in vitro and in vivo anticancer, antiviral, antibiotic, antiprotozoal and antidiabetic activity [23,24,30]. Furthermore, inhibition of enzymes can be achieved as a result of the interaction of POMs with proteins [24,31], making POMs potential drugs for Alzheimer's disease [31].…”
Section: Introductionmentioning
confidence: 99%
“…These molecules are an assemblage of oxo-bridged early transition metals (mostly Mo, W, and V) in their highest oxidation state [13,14]. Their chemical and physical properties can be tuned, giving rise to a large number of possible applications in the fields of catalysis [15][16][17], material science [18][19][20] and medicine [21][22][23][24]. Moreover, the removal of one or more of the addenda atoms from the POM framework results in the formation of a lacunary species, which can coordinate different metal ions, resulting in the formation of metal-substituted POMs [11,25].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Decavanadate is a homoleptic isopolyoxovanadate that interacts with high affinity with several proteins such as myosin, actin, and Ca 2+ -ATPase, thus affecting a range of cellular processes, including calcium homeostasis, muscle contraction, cytoskeleton dynamics and mitochondrial oxygen consumption. [4][5][6][7][8][9][10][11] Furthermore, the antidiabetic, anti-virus, anti-bacterial and anti-tumor activities of V 10 and vanadate compounds are attracting increasing interest. [12][13][14][15][16][17][18] Decavanadate also exhibits insulin-mimetic behavior, and it was shown that, upon incubation with decavanadate, rat adipocytes accumulate much more glucose than with well-established mimetic agents such as BMOV.…”
Section: Introductionmentioning
confidence: 99%